Influence of lipid concentration on encapsulation and particle size in the development of liposomal irinotecan - A. V. Stadnichenko; Y. M. Krasnopolsky; T. G. Yarnykh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Purpose. For creation of liposomal irinotecan form, the influence of lipid concentration on the encapsulation of the active substance and nanoparticle size was necessary to investigate.